Electron-, proton-, and photon-induced spectroscopic changes in chromophore-quencher tricarbonyl(2,2′-Bipyridine)rhenium(I) complexes with 4,4′-azobis(pyridine) - Pourrieux, Gaston (2010)
We report in this work the synthesis and characterization of new mono- and dinuclear complexes of formulas: [Re(bpy)(CO)3(4,4′-azpy)] (CF3SO3), 1 (bpy = 2,2′-bipyridine, 4,4′-azpy = 4,4′-azobis(pyridine)); [(bpy)(CO)3Re(4,4′-azpy) Ru(NH3)5](PF6)3.CH 3CN•6H2O, 2 and the heterodinuclear species [(bpy)(CO)3Re(4,4′-azpy)Ru(NH3)5] 4+, 3 (obtained in situ by electrochemical oxidation of 2). The molecular structure of 1 has been determined by X-ray diffraction. We also report the effect of controlled potential electrolysis, protonation, and light excitation on the absorption and emission properties of these complexes. In particular, complex 1, which is almost non-emissive at room temperature, recovers luminescence either by reduction of coordinated 4,4′-azpy or by trans- to cis-photoisomerization. The detected emission of 1 at 77 K is due to decay from a Re→ bpy metal-to-ligand charge transfer excited state. Time dependent density functional theory calculations support the interpretation of the photophysical changes induced by external stimuli.